The Power of Collective Bargaining: International Rights in a Neoliberal Age - Hendy, John (Unions Matter: Advancing Democracy, Economic Equality, and Social Justice, 2014)
[Provides] an international perspective on the role of liberalism. [The author argues that] a series of international labour law instruments remain in place to protect basic rights to strike and to collective bargaining, all of which can be employed to protect against the tide of neoliberalism. --Introduction
Keywords: Canada; Canadian Foundation for Labour Rights; Democracy; Employee rights; Equality; Labor movement; Labor unions; Social aspects; Social justice